Relation between bile acid reflux into the stomach and the risk of atrophic gastritis and intestinal metaplasia: A multicenter study of 2283 cases. Issue 5 (29th January 2013) - Matsuhisa, Takeshi; Arakawa, Tetsuo; Watanabe, Tetsuo; Tokutomi, Tadashi; Sakurai, Kouichi; Okamura, Seisuke; Chono, Shinji; Kamada, Tomoari; Sugiyama, Atsushi; Fujimura, Yoshinori; Matsuzawa, Kenji; Ito, Masanori; et al.
Abstract : Background: The relationship between bile acid reflux into the stomach and the risk of atrophic gastritis and intestinal metaplasia is still not well understood. Towards obtaining a better understanding, concentrations of bile acids were measured. Patients and Methods: This study was carried out with the participation of 14 facilities in Japan, and 2283 samples were collected. The subjects with bile acid concentrations equal to or higher than the limit of detection were divided into four groups of equal size (group A: 0–25%, group B: 26–50%, group C: 51–75%, and group D: 76–100%). Thus, including the control group, there were five groups in total. The odds that the control group would develop atrophic gastritis and intestinal metaplasia was set as 1, and the odds ratios (OR) in groups A, B, C and D were calculated based on the odds in the control group. Results: Regarding the development of atrophic gastritis, no increased risk was observed in either the Helicobacter pylori ( H. pylori )‐positive or ‐negative cases. The OR for the development of intestinal metaplasia were significantly higher, for both cases with and without H. pylori infection, in group D. Conclusion: High concentrations of bile acid seem to be associated with an elevated risk of intestinal metaplasia.